The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4132/jptm.2017.03.17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unsatisfactory Samples from Conventional Smear versus Liquid-Based Cytology in Uterine Cervical Cancer Screening Test

Abstract: BackgroundCervical cytology for uterine cervical cancer screening has transitioned from conventional smear (CS) to liquid-based cytology (LBC), which has many advantages. The aim of this study was to compare the proportion of unsatisfactory specimens from CS versus LBC at multiple institutions including general hospitals and commercial laboratories. MethodsEach participating institution provided a minimum of 500 Papanicolaou (Pap) test results for analysis. Pap tests were classified according to the participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
2
23
0
1
Order By: Relevance
“…Although conventional cytology has been replaced by LBC testing as the primary test method in the majority of developed countries within the last 10 to 15 years, it remains an option for women in China. Numerous earlier studies have compared the performance of LBC with conventional cytology and demonstrated the advantages of LBC, including increased sensitivity, lower rates of unsatisfactory slides, and the ability to perform HPV DNA testing on the same specimen . However, others also addressed the issue of decreased specificity with LBC and the cost of follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Although conventional cytology has been replaced by LBC testing as the primary test method in the majority of developed countries within the last 10 to 15 years, it remains an option for women in China. Numerous earlier studies have compared the performance of LBC with conventional cytology and demonstrated the advantages of LBC, including increased sensitivity, lower rates of unsatisfactory slides, and the ability to perform HPV DNA testing on the same specimen . However, others also addressed the issue of decreased specificity with LBC and the cost of follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, liquid‐based cytology (LBC) has become a useful cytopathological method for diagnosis. In the early 2000s, the LBC method began to be used widely, especially in gynecological malignancies . LBC has advantages in that uniform specimens can be prepared, drying is avoided, and there is less sample loss.…”
Section: Introductionmentioning
confidence: 99%
“…LBC has advantages in that uniform specimens can be prepared, drying is avoided, and there is less sample loss. Consequently, fewer unsatisfactory specimens are produced . Therefore, the use of LBC specimens for the clinical diagnosis of respiratory malignancies also is expected …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations